2015
DOI: 10.1021/acs.biochem.5b00782
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Substrate Waters between the Closed and Open Cubane Conformers during the S2 to S3 Transition in the Oxygen Evolving Complex

Abstract: A crucial step in the mechanism for oxygen evolution in the Photosystem II complex resides in the transition from the S2 state to the S3 state of Kok–Joliot’s cycle, in which an additional water molecule binds to the cluster. On the basis of computational chemistry calculations on Photosystem II models, we propose a reorganization mechanism involving a hydroxyl (W2) and a μ2-oxo bridge (O5) that is able to link the closed cubane S2B intermediate conformer to the S3 open cubane structure. This mechanism can rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 50 publications
11
90
3
2
Order By: Relevance
“…Substrate analogues are instead found either on Mn4 or at the endpoint of the O4 channel, implying that this channel may be the only one involved in substrate delivery and that Mn4 may be the only site involved in substrate binding. This is consistent with recent studies of the S 2 –S 3 progression, 73,134,142,148 which showed that the first component of the S 3 state is a “closed-cubane” structure with a five-coordinate Mn4( iv ) center. 73 The approximately trigonal bipyramidal geometry of the Mn4( iv ) site of this species results in properties such as absorption in the near-IR and high zero-field splitting, 73 similarly to analogous synthetic Mn( iv ) complexes.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Substrate analogues are instead found either on Mn4 or at the endpoint of the O4 channel, implying that this channel may be the only one involved in substrate delivery and that Mn4 may be the only site involved in substrate binding. This is consistent with recent studies of the S 2 –S 3 progression, 73,134,142,148 which showed that the first component of the S 3 state is a “closed-cubane” structure with a five-coordinate Mn4( iv ) center. 73 The approximately trigonal bipyramidal geometry of the Mn4( iv ) site of this species results in properties such as absorption in the near-IR and high zero-field splitting, 73 similarly to analogous synthetic Mn( iv ) complexes.…”
Section: Resultssupporting
confidence: 93%
“…53,54,58,71,121133 S 3 is an integer spin state and interpretation of spectroscopic data is additionally complicated by heterogeneity, related at least in part to structural polymorphism that has only recently began to be understood. 73,134 A more complete understanding of the S 3 state is necessary before one can confidently discuss methanol interaction in terms of atomic structure. Nevertheless, the present work constrains the methanol interaction site to W6 and restricts the question only to how methanol might affect the different possible S 3 forms, or stabilize one of these forms over the others, for example by inhibiting water delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A,C in contradiction to the observed value by SFX (Kern et al ). However, the optimized O (5) ‐O (6) distance by QM/MM is consistent with the calculated values by DFT (Siegbahn , , Cox et al , Capone et al , Krewald et al , Isobe et al , Retegan et al , Pantazis ). The optimized Mn 4(a) ‐Mn 1(d) distance for Mn hydroxide was about 5.3 Å in contradiction to the SFX1 and SFX2 results.…”
Section: Mn‐mn Mn‐o and O(5)‐o(6) Distances In The S3 Intermediates supporting
confidence: 86%
“…The catalytic process is divided in five steps (from S 0 to S 4 ), which have been largely studied by several spectroscopic techniques, such as extended X‐ray absorption fine structure (Robblee et al , Yano et al , Dau et al , Pushkar et al , Kusunoki , Li et al ), X‐ray crystallography (Zouni et al , Loll et al , Guskov et al , Umena et al , Suga et al , , Kern et al , ) and electron paramagnetic resonance (EPR) (Boussac et al , Sjöholm et al , Lohmiller et al , Boussac et al ). Additionally, in the last years, several theoretical studies have been carried out with the aim to interpret and rationalizing the huge amount of experimental data and ultimately to shed light on the catalytic mechanism of PSII (Ames et al , Isobe et al , Siegbahn , , Askerka et al , , Capone et al , , Narzi et al , ). A detailed characterization of the structural, electronic and magnetic features for each step of the Kok‐Joliot's cycle would represent an important source of inspiration for developing new efficient artificial devices performing the water splitting reaction (Nocera , Faunce et al ).…”
Section: Introductionmentioning
confidence: 99%